Identifying the e-health prevalence and influence pattern: A cross-sectional study - Gurparvesh Singh Goraya; Bhawna Sahota; Sidakbir Singh Paul; Birinder Singh Paul; Gunchan Paul (Journal of Family Medicine and Primary Care)
Background: Internet has transformed healthcare by providing unparalleled access to medical information, resources and support. Objective: This study explores the prevalence, reasons why people turn to the Internet for their healthcare information needs, and highlighting potential benefits, limitation of their assessments experiences. Methods: This study was conducted amongst OPD visiting tients through a pre-validated questionnaire. Subjects were divided into 2 groups:patients through a pre-validated questionnaire and subjects were divided into 2 groups, Internet Use Before Doctor’s Consultation (IBD) and Internet Use After Doctor’s Consultation (IAD). Results: Out of 957 study participants, > 57% agreed to have used internet for health information. More than half of them were young whereas elderly relied solely on doctors. Most common reasons were to know the status of health, management of the disease, or cause of the disease. The e-Health seeking was beneficial for both the groups and improved doctor-patient relationship but more so for IAD group (p<0.0001). Conclusion: This study had tried to address the gap in the literature regarding e-Health prevalence patterns for seeking health information, and also observed that how e-Health seeking affects people’s actions, behavior, and feelings. Results can give insight to professionals on this issue and prepare them to collaborate, facilitate, or empower patients to access and manage health information online. Physicians should ensure they provide patients with essential information during consultations, empowering them to effectively evaluate medical information encountered through e-health platforms.